Practical Significance of Abbreviations in Lexicographic Sources - Khurramova Zarnigor Zhurakulovna (European Science Publishing, 2023)
This article describes lexicographic sources and opinions about lexicography, highlighting the practical importance of abbreviations in lexicographic sources. The width of the possibilities of the dictionary composition of the language is revealed.
Keywords: applied lexicography, local language, Sumerian language, abbreviations, graphic abbreviation, alphanumerics, acronyms.